Analysis of Waiting Period for Men after Divorce Perspective of Jamaluddin Aṭiyah's Maqaṣid Sharia Theory - Hasanuddin Hasanuddin; Muhammad Syukri Albani Nasution; Imam Yazid (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2021)
The Director General of Islamic Religious Institutional Development again issued Circular Number P-005 / DJ. III/Hk.00.7/10/2021 concerning marriage during the iddah period, according to the provisions of the circular